Facilities location models for a shared biodigestion plant - Lyra, Alex Sander [UNESP]; de Oliveira, Paulo André; Cervi, Ricardo Ghantous; de Oliveira Florentino Silva, Helenice [UNESP]; Rodrigues, Sergio Augusto (My University, 2023)
Logistics is increasingly shown to be essential for agribusiness, given that rural producers are concerned with minimizing costs related to the various processes on the properties. Logistic processes involve economic and environmental costs due to high fuel consumption. This article aims to investigate the best location for the implementation of a shared biodigestion center, in order to minimize the distances to be covered by vehicles that will collect organic waste in different locations, aiming at supplying biodigesters for biogas production. The methodology proposed for this approach consists of applying two methods, the center of gravity method and the facility location method (p-medians). Data from geographic coordinates (Latitude and Longitude) and distances between the considered rural producers were used. This methodology made it possible to identify local options for the installation of a shared biodigestion center among rural swine producers in the region of Toledo-PR, in order to optimize the distances and volumes of waste collected and sent to this center. The results showed that this methodology facilitates the process of collecting and disposing of waste generated on the properties, causing producers to minimize transport costs and the total distance covered, while meeting all demand.
Modelos de localização de facilidades para uma central de biodigestão compartilhada
Keywords: Center of gravity, p-median; Modeling; Optimization; Rural waste